Entering a Parallel Universe. - Goth, Gregory; Patterson,, David A. (Communications of the ACM, 2009)
The article discusses the multicore processors that help extend Moore's Law, which states that chip transistor density will double every two years, but may conflict with Amdahl's law, which puts a limit on the benefit of converting code from sequential to parallel. Numerous calculations are performed simultaneously in parallel programming. This operates on the principle that large problems can be divided into smaller ones, which can then be solved at the same time. What to parallelize, the incremental integration of parallel programming, and reconciling the computations of applications with the move to parallel-capable multicore processors are discussed.